LIBRARY AND INFORMATION SCIENCE LITERATURE AND LOTKA’ S LAW - Sen, Bimal Kanti; Taib, Che Azlan; Hassan, Mohd Faris; Sen, B. K.; bin Taib, Che Azlan; Hassan, Mohd Faris (Malaysian Journal of Library and Information Science, 2017)
Attempts to test the validity of Lotka’s law in the domain of library and information science(LIS) taking the annual name index of Library and Information Science Abstracts (LISA) 1992, and annual author index of LISA 1993 as the base, which included 7101 and 7591 abstracts of articles contributed respectively by 8284 and 7664 authors. Lotka’s law is found to be applicable with the value of n as 3.23 in the first case and 3.1 in the second case. It is concluded that the value of n is found to be higher in LIS compared to exact sciences because the number of authors contributing two or more articles are less in this field.